[Rezension von: Hitchcock, David, Vagrancy in English culture and society, 1650-1750] - Sharpe, James (Crime, histoire & sociétés, 2021)
Before the advent of the "New Social History" in the 1960s, conventional wisdom among historians about vagrancy in early modern England was founded on a number of contemporary print commentaries which depicted vagrants as a threat to the well-ordered commonwealth, portraying them as an organised and hierarchical "fraternity of vagabonds" whose values subverted the social norms and values of respectable society.